2003
DOI: 10.1007/s000180300030
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the bioactive peptide PEC-60 in brain

Abstract: PEC-60 is a 60-residue peptide originally isolated from pig intestine. It inhibits glucose-induced insulin secretion from perfused pancreas in a hormonal manner and also has biological activity in the immune system. PEC-60-like immunoreactive material has been reported in catecholamine neurons of the central and peripheral nervous systems, but the peptide has not been identified from that material. We have now isolated PEC-60 from pig and rat brains with a method that combines column purification procedures wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…However, the down-regulation of the protease inhibitor Kazal type 4 (gastrointestinal peptide, PEC-60) in HT-29 cells in response to elevated zinc levels is interesting with respect to its proposed functions. This 60 amino-acid peptide has been originally isolated form the gastrointestinal tract but is also expressed in neurons (Fuxe et al 1994, Norberg et al 2003. The primary function of PEC-60 derived from the gastrointestinal tract is thought to be the inhibition of insulin secretion (Agerberth et al 1989, Ahren et al 1992.…”
Section: Discussionmentioning
confidence: 99%
“…However, the down-regulation of the protease inhibitor Kazal type 4 (gastrointestinal peptide, PEC-60) in HT-29 cells in response to elevated zinc levels is interesting with respect to its proposed functions. This 60 amino-acid peptide has been originally isolated form the gastrointestinal tract but is also expressed in neurons (Fuxe et al 1994, Norberg et al 2003. The primary function of PEC-60 derived from the gastrointestinal tract is thought to be the inhibition of insulin secretion (Agerberth et al 1989, Ahren et al 1992.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that brain metastatic cells from breast cancer and lung cancer induce large amounts of serine protease inhibitors (SERPINs) to prevent plasminogen activator (PA) destruction of L1CAM and mediate the spread of metastatic cells [ 43 ]. SPINK4 has also been demonstrated to play a role in the brain [ 44 ]. Nevertheless, more studies are required to verify whether SPINK4 can activate L1CAM through PA inhibition to drive metastasis and CCRT resistance in rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…SPINK2 (located on 4q12) is expressed in the testis, epididymis, and seminal vesicle, where its antimicrobial function may be involved in protection of fertility (Rockett et al 2004). SPINK4 was originally isolated from pig intestine (Agerberth et al 1989) and is abundantly expressed in human and porcine goblet cells in the crypts of Lieberkühn but was also found in monocytes and in the central nervous system (Metsis et al 1992; Norberg et al 2003). SPINK5 is expressed in the thymus, vaginal epithelium, Bartolin’s glands, oral mucosa, tonsils, and the parathyroid glands (Magert et al 1999).…”
Section: Introductionmentioning
confidence: 99%